EFFECT OF GINGER (Zingiber officinale) ON NAPROXEN INDUCED-LIVER DAMAGE IN WISTAR RATS - Mallo, Mahan Josiah; Nwankwo, Uchechi Amarachi; Toryila, Joseph Emberga; Eje, Victor Inyila; Oladejo, Abiodun Joel; Danborno, Angela Member (FUDMA Journal of Sciences, 2026)
The potential effect of Zingiber officinale on naproxen induced liver damage was evaluated. Twenty-Five male Wistar rats were grouped into five groups of 5 rats each. Liver damage was induced by oral administration of Naproxen 20mg/kg body weight and ginger supplements for 14 days. Group I served as the positive control group; while ginger supplement was included in the diet of group II, III and IV at graded concentration of 20mg/kg, 40mg/kg and 60mg/kg of animal feed and naproxen. Group V received only 20mg/kg of naproxen for 14 days. At the end of the period of administration, the rats were euthanized and their blood was collected and used to determine the levels of Aspartate Transferase, Alanine Aminotransferase, Alkaline Phosphate, direct bilirubin, total protein, albumin, and lactate dehydrogenase. The result obtained revealed a significant increase in serum Aspartate Transaminase in all the groups treated with the various fractions of ginger and the naproxen group as compared to the normal control group. There was also a significant increase in total protein in groups 3,4 and 5 compared to the control group and there was a significance decrease in serum alkaline phosphatase in all groups treated with the ginger. The study also revealed an increased in serum albumin. In conclusion, ginger supplement in diet ameliorates naproxen induced liver damage. It is therefore recommended that ginger should be supplemented in the diets due to its beneficial effects and the abuse of non-steroidal anti-inflammatory drugs should be avoided.